Optical Feedback for Sensitivity Enhancement in Direct Raman Detection of Liquids - Liu, Miao; Mu, Yunyun; Hu, Jingyun; Li, Jiajun; Zhang, Xinping (Journal of Spectroscopy, 2021)
Detection of low-concentration molecules in liquids has been a challenge in sensing technologies. Raman spectroscopy is an effective approach for trace detection, which is in fact a “volume-excitation” and “volume-collection” technique in the analysis of liquid samples. However, for the commonly employed one-pass excitation and back-scattering detection scheme, a large portion of both the excitation laser energy and the Raman-scattering light energy is wasted without efficient reuse or collection. In this consideration, we demonstrate a broadband optical feedback scheme by a curved high-reflection mirror for both the excitation and the Raman-scattering light, so that the excitation and the forward-propagating Raman signal can be back-reflected and collected with a high efficiency. Using the “F+2f” design, where F and f are the focal lengths of the focusing lens and curved reflection mirror, respectively, we were able to not only produce two focuses of the excitation laser beam but also extend the Raman interaction by a doubled distance. For the detection of pure ethanol molecules and the R6G molecules in water with a concentration of 10−3 M, the Raman signal was enhanced by a factor of about 5.6. The optical feedback scheme and discovered optical mechanisms supply effective improvements to the Raman spectroscopic measurements on liquid samples.